DESIGN OF GPS AND COMPASS HELMET VISUAL DATA USING MICROCONTROLLER FOR MARINE FORCE OF INDONESIAN NAVY - Endin Tri Hartanto; Erpan Sahiri; Agung Gunawan; Muhammad Sigit Purwanto (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
The Marines are a component of the combat forces owned by the Navy. In carrying out their duties as infiltration forces and landing forces, sophisticated equipment is needed to support each movement in terms of knowing the position of coordinates in the form of latitude longitude and compass direction to facilitate the movement of troops in carrying out operational tasks. For this reason, a tool was made to visually know the position of the latitude and longitude of the compass, making it easier for troops to carry out their duties both on the training ground and on the battlefield. This tool is in the form of a Design Combat Helmet for Visual Data Viewer GPS and Microcontroller-based Compass for the Navy Navy. This tool uses Arduino Mega Pro Mini 2560 as a microcontroller, V.KEL 2828U7G5LF as a GPS module, HMC5883L as a Compass module and Wemos Oled LCD 64x48 0.66